No Significant Differences between Syndesmotic Fixation and No Fixation in Supination-External Rotation Ankle Fractures - Kuznar, Wayne (MD Conference Express, 2014)
A prospective randomized study [NCT01234493] comparing syndesmotic transfixation and no fixation in patients with intraoperatively confirmed syndesmosis disruption, as discussed in this article.